Élaboration d’une liste de vocabulaire dans un contexte FLE - Lindqvist, Christina; Ramnäs, Mårten (Studia Romanica Posnaniensia, 2023)
In this article, we discuss the elaboration and use of vocabulary lists aimed for learners of French as a for-eign language. These lists are commonly based on corpora, which, in the ideal case, are representative, relevant and large. As for the English language, this kind of corpora has been available for a long time (e.g. the COCA and the BNC). Vocabulary lists, which are often used in learning contexts, have been based on these corpora. The situation is, however, less favorable when it comes to the French language, with fewer corpora meeting the mentioned criteria, and, thus, fewer possibilities to create vocabulary lists that are useful for learners. In this contribution, we present work that has been done in order to create a vocabulary list, Riksprovsordlistan, containing about 4,000 words and used at all Swedish universities. The discussion focuses on methodological challenges such as choice of counting unit – lemma vs. word family –, the role of frequency, thematic vocabulary, as well as characteristics of written vs. spoken corpora.